World watch geography Book 1 A geography course for grade 6 - Moorcroft, Christine (Karachi Oxford University Press, 2024)
It is revised according to the national curriculum of Pakistan 2022. It is an extension of World watch social studies to the lower secondary level. It integrated physical, human and environmental geography with a special focus on Pakistan.
Keywords: Geography